2016
DOI: 10.1021/acs.cgd.6b01283
|View full text |Cite
|
Sign up to set email alerts
|

Two Faces of Ciprofloxacin: Investigation of Proton Transfer in Solid State Transformations

Abstract: Ciprofloxacin (CIP) can exist in two different forms: the zwitterion and the unionized form. While the crystal structure of each has been described independently, the ability of CIP to transform from one to the other in the solid state has not been described. The crystal structures of unionized and zwitterionic CIP were therefore compared using computational methods, including their packing arrangement, hydrogen bonding, packing energy, intermolecular potentials and HOMO/LUMO energy gap. The pure amorphous for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 59 publications
(145 reference statements)
6
54
1
Order By: Relevance
“…As can be seen in Fig. 6, the results showed, in agreement with previous studies, stretching of the carboxyl group in CFX is missing in the region of 1710 cm −1 (23,24). It was suggested that a "betainelike structure" exists where electronic effects become more profound leading to the formation of a zwitterion, on the carboxyl (COOH).…”
Section: Thermal and Spectroscopic Analysis Of Cfx/ta Co-amorphous DIsupporting
confidence: 89%
“…As can be seen in Fig. 6, the results showed, in agreement with previous studies, stretching of the carboxyl group in CFX is missing in the region of 1710 cm −1 (23,24). It was suggested that a "betainelike structure" exists where electronic effects become more profound leading to the formation of a zwitterion, on the carboxyl (COOH).…”
Section: Thermal and Spectroscopic Analysis Of Cfx/ta Co-amorphous DIsupporting
confidence: 89%
“…8. as the critical water activity (a c w ). Since K h is known at a particular temperature, the standard free-energy change for the hydration reaction can be calculated using the following expression: (5) In order to establish the thermodynamic stability ranges of the different crystalline forms of ciprofloxacin and norfloxacin fumarates, solubility experiments in water/methanol mixtures of various compositions were performed. The details of the experimental procedure are provided in the Materials and methods section.…”
Section: Relative Stability Of the Solid Forms And Determination Of Tmentioning
confidence: 99%
“…It was recently demonstrated that the solubility of pure CIP is determined by solid-state issues, since the zwitterionic molecules in their crystal form are held together by strong dipole-dipole interactions. 5 Salt formation changes the state of CIP molecules in their crystal form from zwitterionic to cationic, effectively reducing the lattice energy and improving aqueous solubility. 6 Therefore, a number of efforts have been made to extend the range of fluoroquinolone solid forms and to modify the poor solubility performance of CIP and NFX through salt preparation with different organic acids, including aliphatic [7][8][9][10][11][12] and aromatic carboxylic acids, [13][14][15][16] derivatives of sulfonic acids, and artificial sugars.…”
Section: Introductionmentioning
confidence: 99%
“…respectively. In addition to water loss, TGA analysis also showed that all of the samples undergo significant thermal degradation above ~200 o C. Similar levels of degradation were seen with binary polymeric CIP ASDs (12), and the pure drug is also known to decompose upon melting (2). The thermograms of each of the amorphous samples contained broad endotherms above 180 o C due to melting accompanied by decomposition (Figure 3).…”
Section: Thermal Analysis and Estimation Of Component Miscibilitymentioning
confidence: 71%
“…These oppositely charged groups interact to form chains of molecules, resulting in a strong crystal lattice. CIP therefore exhibits solid-state limited solubility (2). CIP also largely exists in the zwitterionic form in neutral media, with an overall neutral charge, which contributes to its low solubility.…”
Section: Introductionmentioning
confidence: 99%